Micro-nanofiber composite biomimetic conduits promote long-gap peripheral nerve regeneration in canine models - Xianhao Dong; Yueyue Yang; Zheheng Bao; Adam C. Midgley; Feiyi Li; Shuxin Dai; Zhuangzhuang Yang; Jin Wang; Lihua Liu; Wenlei Li; Yayuan Zheng; Siyang Liu; et al. (Bioactive Materials, 2023)
Peripheral nerve injuries may result in severe long-gap interruptions that are challenging to repair. Autografting is the gold standard surgical approach for repairing long-gap nerve injuries but can result in prominent donor-site complications. Instead, imitating the native neural microarchitecture using synthetic conduits is expected to offer an alternative strategy for improving nerve regeneration. Here, we designed nerve conduits composed of high-resolution anisotropic microfiber grid-cordes with randomly organized nanofiber sheaths to interrogate the positive effects of these biomimetic structures on peripheral nerve regeneration. Anisotropic microfiber-grids demonstrated the capacity to directionally guide Schwann cells and neurites. Nanofiber sheaths conveyed adequate elasticity and permeability, whilst exhibiting a barrier function against the infiltration of fibroblasts. We then used the composite nerve conduits bridge 30-mm long sciatic nerve defects in canine models. At 12 months post-implant, the morphometric and histological recovery, gait recovery, electrophysiological function, and degree of muscle atrophy were assessed. The newly regenerated nerve tissue that formed within the composite nerve conduits showed restored neurological functions that were superior compared to sheaths-only scaffolds and Neurolac nerve conduit controls. Our findings demonstrate the feasibility of using synthetic biophysical cues to effectively bridge long-gap peripheral nerve injuries and indicates the promising clinical application prospects of biomimetic composite nerve conduits.